2021
DOI: 10.3390/jcm10163655
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Psychiatric and Cognitive Symptoms in West Asia, South Asia and Africa: A Systematic Review and Meta-Analysis

Abstract: Recent research has shown that the prevalence of stroke incidents and the number of survivors in developing countries surpass those from developed countries. This study aimed to enumerate the prevalence of post-stroke psychiatric and cognitive symptoms among stroke survivors from West and South Asia and Africa through a systematic review and meta-analysis. Data from each country was systematically acquired from five major databases (PsycINFO, Web of Science, Scopus, PubMed/Medline, and Google Scholar (for any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…While there is an abundance of research on cognitive symptoms secondary to stroke from many industrialized countries, 10 little has been forthcoming from developing countries, despite having a high prevalence of stroke. In this study, we aimed to conduct an epidemiological investigation from 563 stroke centers in China to describe the cognitive status of first-ever stroke patients and risk factors related to PSCI.…”
Section: Introductionmentioning
confidence: 99%
“…While there is an abundance of research on cognitive symptoms secondary to stroke from many industrialized countries, 10 little has been forthcoming from developing countries, despite having a high prevalence of stroke. In this study, we aimed to conduct an epidemiological investigation from 563 stroke centers in China to describe the cognitive status of first-ever stroke patients and risk factors related to PSCI.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that disruption of connections in the cognitive and limbic systems [71] caused by the vascular accident could explain the relationship between post-stroke depression and cognitive impairment. Specifically, poststroke depression and executive dysfunction could result from functional overconnectivity between the default mode and salience/cognitive control networks and reduced crosshemispheric frontoparietal functional connectivity [16]. Lastly, it is theoretically possible that post-stroke depression and cognitive impairment are independent phenomena for some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Depression occurs in around 30% of stroke survivors [16][17][18]. Although not consistent across all studies [18,19], depression negatively impacts post-stroke patients.…”
Section: Introductionmentioning
confidence: 94%
“…The search strategy is shown in the S1 Search Strategy. Eleven systematic reviews identified were hand-searched for relevant studies [3][4][5][6][7][8][17][18][19][20][21].…”
Section: Search Strategy and Data Extractionmentioning
confidence: 99%